2017
DOI: 10.1007/s12678-017-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ethanol Oxidation Reaction on Pt (PtSn)-Activated Nickel Foam Through In situ Formation of Nickel Oxy-Hydroxide Layer

Abstract: The present paper reports on a significant enhancement of ethanol oxidation reaction (EOR), investigated on Pt and PtSn-modified nickel foam electrodes, realized via in situ formation of surface nickel oxy-hydroxide layer in 0.1 M NaOH solution. In the presence of ethanol in electrolyte, adsorbed C 2 H 5 OH molecules (and/or its oxidation intermediates) prevent Pt (PtSn) sites from their extensive dissolution upon prolonged surface electrooxidation of Ni foam electrode. The above was elucidated through cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The magnitude of the backward peak is less than that of the forward peak in an alkaline medium. This is because the removal of adsorbed carbonaceous species is easier due to the availability of oxygen-containing species that facilitate quick ethanol oxidation [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the backward peak is less than that of the forward peak in an alkaline medium. This is because the removal of adsorbed carbonaceous species is easier due to the availability of oxygen-containing species that facilitate quick ethanol oxidation [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) results are presented in the form of Nyquist plots in Figure b. The Nyquist plots consist mainly of semicircles, the diameter of which corresponds to the value of the charge transfer resistance of the EOR. The lack of a line at 45° in the lower frequency range suggests that the electron transfer resistance is predominant and that impedance of diffusion is rather negligible. , It is observed that in the examined alcohol concentration range, charge transfer resistance decreases with increasing ethanol concentration. An equivalent circuit model consisting of an ohmic resistance of the electrolyte, R s , a constant phase element, CPE dl , which represents experimental double-layer capacitance, C dl , and an ohmic resistance of the charge transfer, R ct (inset in Figure b) was fit to each EIS spectrum, and the values of R ct obtained from the fitting are 139, 93, and 60 Ω for 0.5, 1, and 3 M EtOH, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This can be ascribed to an expansion in OH ad sites at the higher potential which oxidizes the adsorbed intermediates, along these lines authorizing the metal destinations to facilitate oxidation [64]. From the Nyquist plots, ethanol and methanol oxidation is typically denoted by frequency inductive circle with a diameter representing charge transfer resistance (R ct ) [65,66]. In Figure 10(a) and 10(b), the radius of the arc reflects the charge transfer resistance (R ct ) between the surface of the electrode and the electrolyte when ethanol and methanol is oxidized on the surface of the electrode.…”
Section: Electrochemical Impedance Study (Eis)mentioning
confidence: 99%